A review of in vitro and in vivo methods and their correlations to assess mouthfeel of solid oral dosage forms. Issue 3 (March 2021) - Asiri, Abdullah; Hofmanová, Justyna; Batchelor, Hannah
Graphical Abstract: Highlights: Sensory perception is crucial for acceptability of solid oral dosage form pharmaceutical products. A range of in vivo and in vitro methods are used to measure mouthfeel of oral medicines. Correlating in vivo and in vitro data helps to understand mouthfeel perception and design better tests. Current strategies for sensory assessment require standardisation. The oral sensory perception of medicines is an important quality attribute that can influence adherence to medication. A systematic review identified studies reporting both in vitro and in vivo data on the mouthfeel of solid oral dosage forms. Fifty-six studies were identified and included in the analysis. Orodispersible tablets were the most commonly studied formulation (32/56 studies). In vivo studies were typically conducted using untrained healthy adult volunteers, where sample sizes ranged from 3 to 75 participants. Only eight studies reported a numeric correlation between the in vitro and in vivo data presented. In this review, we highlight opportunities for the development of a standardised approach to the assessment of mouthfeel to enable the development of optimised oral pharmaceutical products. Teaser: This review analyses the relationship between instrumental and human data used to assess the mouthfeel of solid oral dosage forms to provide recommendations on the most appropriate methods to use in future studies.